FDI in investment banking - Gulamhussen, M. A. (Thunderbird International Business Review, 2012)
The determinants of foreign direct investment (FDI) in investment banking are tested using unique data obtained from 43 semistructured interviews with senior managers of multinational banks. Consistent with internalization theory, the decision to service new customers is positively and significantly related to FDI. In line with internalization theory and the sequential entry framework, the perceived risk of doing business abroad is negatively and significantly related to FDI. Lock-in is positively and significantly related to FDI. Very few managers consider it important to follow domestic customers, which does not emerge as significantly related to FDI. Qualitative information facilitated the interpretation of multiple empirical estimations.